The Influence of Using a Website on the Level of Knowledge of the International Handball Law among the Students of the College of Sport Sciences at Mutah University (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to identify the influence of using a website on the level of knowledge of the international law of handball among the students of the College of Sports Sciences at Mutah University. The researchers used the experimental method and the study sample consisted of (40) students from the College of Sport Sciences who were selected using a simple random method. They were divided into two groups, an experimental and a control group, with (20) students in each group, and the researcher designed a website to teach the international handball law. A test was used to measure the level of the cognitive outcome, which was built by Shaalan (2019). The following statistical methods were used: arithmetic averages, Pearson correlation coefficient, frequencies and percentages, and T-test.The results of the study found that using  a website in presenting the international law of handball by three meetings per week for six weeks has a positive effect in improving the cognitive outcome of the learners.The study recommends using the website designed in teaching the international law of handball.
Keywords: Knowledge Base; Website